Fat Reduction and Replacement in Dry-Cured Fermented Sausage by Using High Pressure Processing Meat as Fat Replacer and Olive Oil - Bolumar Tomas; Toepfl Stefan; Heinz Volker (Polish Journal of Food and Nutrition Sciences)
The present paper describes the modification of the lipid fraction of dry-cured fermented sausage through fat reduction (35%) and fat replacement of animal fat with olive oil (up to 10%). High pressure processing (HPP) treated meat was employed as a novel fat replacer to reduce the fat content and as a new strategy to enable a stable incorporation of olive oil in dry-cured fermented sausages. Chemical (proximate composition and fatty acid profile), physical (water retention, structure formation and colour) and sensorial (appearance, texture and flavour) properties were evaluated. It is concluded that 35% of fat reduction is possible without reduction of consumer acceptability. Moreover, the addition of HPP-treated meat as a fat replacer resulted in good mimic of the fat particles together with good physical and sensory properties. Therefore, it resulted in an effective and clean alternative (no added-additives) for fat reduction. However, the incorporation of olive oil either by direct addition (4.3% oil) or within a HPP-created protein network (10% oil) resulted in unacceptable products since the oil was not properly retained inside the sausage matrix. Further studies are needed to find processing strategies that permit a stable incorporation of liquid plant oils to dry-cured fermented sausage for the development of healthier and more sustainable dry-cured fermented meat products.